PEMBIAYAAN SYARIAH DALAM MENDUKUNG PERDAGANGAN GLOBAL: KAJIAN PRINSIP SYARIAH DAN REGULASI INTERNASIONAL - Johan Dwi Sutikno; Hania Nuril Aida Rochmah; Rokhmat Subagiyo; Muhammad Aswad; Qomarul Huda (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2025)
This study explores the role of letters of credit in supporting global halal trade and how they are regulated in international markets, focusing on halal product exports and the factors that influence them in the context of global economic uncertainty. This article aims to analyze how global economic uncertainty can affect the continuity of halal product exports and imports and how L/C contributes to reducing financial risks and strengthening the competitiveness of the halal industry in the international market. This study uses a qualitative approach based on previous research obtained from the Publish or Perish and Google Scholar databases between 2020 and 2025, resulting in 19 relevant articles that were analyzed using a narrative review approach. Furthermore, this has led to a finding that shows that the potential of the global halal industry market has increased significantly, mainly driven by the number of Muslims worldwide, as well as halal lifestyle behaviors and halal awareness, which are also key factors. Then, companies that openly engage in the export and import of halal products using sharia L/C financing are not yet widely found. Furthermore, from a sharia perspective, the application of letters of credit refers to the DSN-MUI fatwa on Sharia Import L/C. The findings of this study are expected to provide insights for business actors and regulators in optimizing the use of L/C as a financial instrument that supports halal trade in accordance with sharia principles and international regulations.